Relationship of work-family conflict, work-life Imbalance, and work-related stress with employee performance of married women In Indonesia: A cross sectional study - Datu Razali Datu Eranza; Mahmoud Ali Rababah; Ahmad Nurkhin; Christian Wiradendi Wolor (Iranian Journal of Psychiatry and Clinical Psychology, 2023)
This study aims to assess the relationship of work-family conflict (WFC), work-life imbalance, and work-related stress with the performance of working women in Indonesia. This is a quantitative cross-sectional study using structural equation modeling. The participants were 404 married female workers in Indonesia. A research-made questionnaire was used to collect data. The data were analyzed in Smart PLS software version 3. The results showed that WFC had a significant relationship with work-related stress, and work life imbalance had a significant relationship with work-related stress. The WFC had no significant relationship with employee performance. The work-life imbalance had no significant relationship with employee performance, either. Finally, work-related stress had a negative significant relationship with employee performance. Conclusion Organizational and managerial support can help working women achieve an effective harmony between work and family roles.